Moral Values of Early Adolescents: Conative Level - Vaičekauskiene, Snieguole (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The most intensive education of moral values takes place in adolescence, and thus the family and school have to make big efforts for the internalization of moral values. The article reviews the opinions of teachers and parents of 5 – 6th grade pupils and analyses the conative (behaviour) level of moral attitudes among early adolescents. The survey showed that early adolescents are self-critical; they assess their moral behaviour stricter than the behaviour of their peers, whereas the teachers assess the moral behaviour of teenagers stricter than pupils or their parents.